Penerapan Metode Weigth Product Untuk Rekomendasi Penempatan Praktek Kerja Industri (Study Kasus: SMK Muhammadiyah 01 Pekanbaru) - Doni Winarso; Fitri Nurita; Syahril Syahril (Ikatan Ahli Informatika Indonesia (IAII), 2018)
This research aims to build a decision support system (DSS), that is used to recommend a place of Industrial Practice (in Indonesia known as PRAKERIN) for students who will plunge into the world of industrial world (DUDI). The reason why this research is raised is due to the frequent difficulties faced by students in determining which location suits their needs. In this research, location selection is calculated using weighted product (WP) method. WP method is one of Multiple Criteria Decision Making (MCDM) method that can solve one dimensional and multi dimensional problems. From the results of research conducted found that the WP method can help determine the location prakerin for students, so for students it is very helpful to them in determining prakerin location in accordance with the criteria specified.